1985
DOI: 10.1161/01.res.56.1.146
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipase D produces increased contractile force in rabbit ventricular muscle.

Abstract: SUMMARY. Inclusion of phospholipase D (Streptomyces chromofuscus, 5 U/ml) in the medium perfusing rabbit papillary muscles increased peak force development by 78% and peak dF/dt by 89%. The maximal contractile response occurred 40-50 minutes after addition of the enzyme to the perfusate. As peak contractile response developed, aftercontractions appeared in most muscles. The inotropic response was slowly reversible, with disappearance of aftercontractions, upon discontinuation of the enzyme. Phospholipase D pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

1985
1985
2004
2004

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…A role for SL PLD and its hydrolytic product, PA, in cardiac function has been indicated in a number of studies [27][28][29][30]. For example, the cardiac SL Na + -Ca 2+ exchanger activity has been shown to be increased with the treatment of the membranes with exogenous PLD [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A role for SL PLD and its hydrolytic product, PA, in cardiac function has been indicated in a number of studies [27][28][29][30]. For example, the cardiac SL Na + -Ca 2+ exchanger activity has been shown to be increased with the treatment of the membranes with exogenous PLD [28].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the cardiac SL Na + -Ca 2+ exchanger activity has been shown to be increased with the treatment of the membranes with exogenous PLD [28]. Such a treatment has also been shown to increase Ca 2+ -binding and force of contraction of the heart [29]. The observation that exogenous addition of PA or PLD generates Ca 2+ -dependent slow action potentials in depolarized rat atrium supports the role of PA in mediating the increase of Ca 2+ influx into the cardiac cells [30].…”
Section: Discussionmentioning
confidence: 99%
“…(4) Phospholipase D (PLD) cleaves the nitrogenous base from sarcolemmal phospholipids with the production of anionic phospharidic acid. PLD treatment increases Ca ++ bound to whole, cells (Burt et al, 1984) and to purified sarcolemma (Langer and Nudd, 1983) and increases force development of ventricular tissue from both neonatal rat (Burt et al, 1984) and adult rabbit (Langer and Rich, 1985) by 80-150%. (5) Finally, charged amphiphiles, used as phospholipid analogues, modulate interaction of calcium with myocardial sarcolemma (Philipson et al, 1984).…”
mentioning
confidence: 99%
“…For example, exogenous phospholipase D increased the contractility of neonatal rat ventricular tissue35 and produced positive inotropy in rabbit papillary muscle. 36 Philipson and Nishimoto'6 demonstrated that exogenous phospholipase D stimulated Na+-Ca2' exchange in cardiac sarcolemmal vesicles, which was accompanied by an increase of phosphatidic acid in the sarcolemma. Depending on the intracellular and extracellular Na+ and Ca21 concentrations and the membrane potential, this bidirectional transport mechanism could elevate cytosolic calcium and thereby increase contractility.…”
Section: Discussionmentioning
confidence: 99%